PEMANFAATAN BUAH TERUNG BELANDA DAN KULIT PISANG KEPOK DALAM PEMBUATAN SELAI - Yudi ' Sutriono; Usman ' Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to obtain the ratio of the addition of “belanda eggplant” on the quality of the jam of “kepok banana peel”. Research was carried out by using a Complete Randomized Design (CRD), with 5 treatments and 3 repetitions to obtained 15 experimental units. The treatments were PT0 (60% pureed of kepok banana peel and 0% pureed of  belanda eggplant), PT1 (50% pureed of kepok banana peel and 10% pureed of belanda eggplant), PT2 (40% pureed of kepok banana peel and 20% pureed of belanda eggplant), PT3 (30% pureed of kepok banana peel and 30% pureed of belanda eggplant) and PT4 ( 20% pureed of kepok banana peel and 40% pureed of belanda eggplant). Data were analyzed statistically using ANOVA and DMRT at 5% level. The results show that the ratio of belanda eggplant and kepok banana peel significantly affected all parameters. The best treatment was PT4 (20% pureed of kepok banana peel and 40% pureed of belanda eggplant) with a moisture content of 28,71%, ash content of 0,21%, viscosity 736,28 (cP), the fiber content of 0,51% and total sugar content 48.02%. Sensory test of jam from best treatment had red colour, somewhat flavorful belanda eggplant  and kepok banana peel, sweet taste slightly sour, soft texture and overall assessment preferred by the panelists.     Keywords: Jam, Belanda Eggplant and Kepok Banana Peel.